A Case of Ovarian Pregnancy Diagnosed by MRI - Shingo Io; Masaaki Hasegawa; Takashi Koyama (Hindawi Limited, 2015)
Ovarian pregnancy is a rare form of ectopic pregnancy, causing a great diagnostic challenge. We report a case of ovarian pregnancy in a 42-year-old woman, in whom MRI successfully demonstrated the implantation in the ovary. Transvaginal ultrasonography showed an echogenic mass in the right ovary but failed to demonstrate tubal pregnancy. T2-weighted MR images disclosed a gestational sac structure in the right ovary, which exhibited heterogeneous high intensity intermingled with punctate foci of distinct low intensity. MRI may be a useful tool for diagnosing ovarian pregnancy, by demonstrating a gestational sac in the ovary.